Pengaruh Rasio Keuangan terhadap Perubahan Laba pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2009-2013 - Ramadhan, Bahtiar; Handayani, Dwi; Purbandari, Theresia (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2018)
This study examined the influence of financial ratios to changes in earnings at companies listed in Indonesia Stock Exchange (IDX) 2009-2013. This study aims to provide empirical findings about the influence of financial ratios to changes in earnings at companies listed in Indonesia Stock Exchange (IDX) 2009-2013. This study uses keuagan statements audited companies listed in Indonesia Stock Exchange 2009-2013 period. The sample in this study as many as 32 ​​companies of 153 companies listed Indonesian Stock Exchange. The data used in the audited financial statements are the balance sheet and income statement. The sampling technique is purposive sampling. The results of the analysis using SPSS 17, it can be concluded that the current ratio, quick ratio, debt to equity ratio, debt to total assets, total asset turnover, inventory turnover does not significantly influence the changes in earnings, and net profit margin significant positive effect on earnings changes.